Impact of preexisting diabetes mellitus on transplantation outcomes in hematopoietic stem cell transplantation. (February 2015) - Radfar, Mania; Faghihi, Toktam; Hadjibabaie, Molouk; Ebrahimi, Faeze; Qorbani, Mostafa; Iravani, Masoud; Ghavamzadeh, Ardeshir
Abstract New onset diabetes mellitus is frequently observed following hematopoietic stem cell transplantation (HSCT) and is associated with adverse transplantation outcomes. However, the outcomes of patients with preexisting diabetes mellitus undergoing HSCT are largely unknown. We aimed to explore the impact of preexisting diabetes on transplantation outcomes in HSCT. In a retrospective study, medical charts of 34 HSCT recipients with diabetes mellitus undergoing allogeneic or autologous transplantation were reviewed and compared with 71 HSCT recipients without diabetes. Primary outcome was overall survival. Secondary outcomes included hematopoietic recovery, length of hospital stay, febrile neutropenia, acute and chronic graft-versus-host disease (GVHD), primary disease recurrence, and non-relapse mortality (NRM). On univariate analysis, there was no difference in transplantation outcomes in recipients with diabetes compared with recipients without diabetes. However, after adjusting for potential covariates, multivariate analysis demonstrated that having diabetes before HSCT significantly predicted outcome and decreased overall survival (hazard ratio 0.51, 95% confidence interval: 0.27–0.97, p value: 0.04). This study suggests that patients with diabetes mellitus undergoing allogeneic or autologous HSCT may have inferior survival rates and warrant further attention.